Artist Olexander Borodai: An Innovator in the Field of Hot Enamel and Monumental Art - Mostovshchykova, Daria; Mykhalevych, Viktor (Journal of History Culture and Art Research, 2020)
The article is dedicated to the work of the artist Oleksander Andriyovych Borodai, an enameller who made transformations in the field of hot enamel in the late 20th – early 21st centuries in Ukraine, and whose name is associated with the transition from miniature decorative to experimental forms in the use of hot enamel. His works, including easel and monumental compositions, installations, art objects, sculptures, and jewelry, are a unique phenomenon that has no analogs in Ukraine and stands out against the backdrop of enamel work on a global scale. The purpose of this publication is to reveal the personality of Mr. Borodai as an artist, enameller, and teacher. To attain this objective, the publication reveals the main dates and facts in chronological order from the biography of the artist, which contributed to his formation as a leading enameller in Ukraine. At present, the works of the above-mentioned author, made in the technique of hot enamel, have gained significant importance in the field of construction and architecture. Due to the anti-corrosion properties and strength of the material, which retains its color despite weather conditions, the interior and exterior works of Mr. Borodai acquire particular significance as figurative and artistic dominants of large cities of Ukraine. As a result, it is emphasized that O. Borodai has become a phenomenon of modern enamel art. He left a significant creative legacy and students who continue to promote the enamel work at home and abroad. It was revealed that in the conditions of formation of the Ukrainian art market and taking into account active integration into the European art space, the artist’s work has become a kind of cultural asset of Ukraine, which requires deeper research and systematization.